India : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses outlook and risk related to the economic development of India. The Indian economy is on a recovery path, supported by a large terms of trade gain (about 2 1\2 percent of GDP) and reduced external vulnerabilities, though downside risks remain. Important economic and structural reforms have been initiated, but further reforms are needed to boost India's growth potential. Notwithstanding the cyclical pickup, medium-term growth continues to be constrained by supply-side bottlenecks and weaknesses in the corporate and banking sectors. Past fund advice and the authorities' macroeconomic policies have been broadly aligned, but progress on structural reforms has been partial.